Escala de Uso Problemático Generalizado del Internet 2: adaptación para adultos de Buenos Aires - Stover, Juliana Beatriz; Fernández Liporace, María Mercedes; Castro Solarno, Alejandro (Pontificia Universidad Católica del Perú, 2023)
The Generalized Problematic Internet Use Scale 2 was adapted for the adult population of Buenos Aires. Participants were 225 subjects (68.4% female; 30.7% male, 0.9% non-binary). Instruments administered were: survey of sociodemographic data and characteristics of use of social networks; Generalized Problematic Internet Use Scale 2; Mental Health Continuum Short Form and; Symptom Check List-27. Confirmatory factor analysis was carried out; It was found an adequate fit of the structure proposed by the original author. Cronbach’s and ordinals alphas ranged from .77 to .87. Significant positive correlations were found between the generalized problematic use of the Internet, the psychopathological symptoms and the time of use of social media. Associations were negative with psychological well-being.

Se adaptó la Escala de Uso Problemático Generalizado del Internet 2 para población adulta de Buenos Aires. Los participantes fueron 225 sujetos (68.4% mujeres; 30.7% varones, 0.9% no binarios). Los instrumentos fueron: encuesta de datos sociodemográficos y de características de uso de redes sociales; Generalized Problematic Internet Use Scale 2; Mental Health Continuum Short Form y; Symptom Check List 27. Mediante análisis factoriales confirmatorios se halló adecuado ajuste de la estructura propuesta por el autor original. Los coeficientes alfas de Cronbach y ordinales se ubicaron entre .77 y .87. Se encontraron correlaciones positivas significativas entre el uso problemático generalizado de Internet, la sintomatología psicopatológica y el tiempo de uso de redes sociales. Las asociaciones fueron negativas con el bienestar psicológico.

L’échelle d’utilisation problématique généralisée d’Internet 2 a été adaptée pour la population adulte de Buenos Aires. Les participants étaient 225 sujets (68,4% de femmes ; 30,7% d’hommes, 0,9% de non-binaires). Les tests administrés étaient: enquête sur les données sociodémographiques et les caractéristiques d’utilisation des réseaux sociaux ; Échelle d’utilisation problématique généralisée d’Internet 2 ; continuum de la santé mentale MHC-SF ; liste de contrôle des symptômes 27 (SCL-27). Grâce à une analyse factorielle confirmatoire, un ajustement adéquat de la structure proposée par l’auteur original a été trouvé. Les coefficients alpha de Cronbach et ordinaux étaient compris entre 0,77 et 0,87. Des corrélations positives significatives ont été trouvées entre l’utilisation problématique généralisée d’Internet, les symptômes psychopathologiques et le temps d’utilisation des réseaux sociaux. Les associations étaient négatives avec le bien-être psychologique.

A Escala de Uso Problemático Generalizado 2 da Internet foi adaptada para a população adulta de Buenos Aires. Os participantes foram 225 indivíduos (68.4% mulheres; 30.7% homens, 0,9% não binários). Os instrumentos administrados foram: pesquisa de dados sociodemográficos e características de uso das redes sociais; Escala de uso problemático generalizado da Internet 2; Contínuo de Saúde Mental (MHC-SF); Lista de verificação de sintomas-27 (SCL-27). Foi realizada a análise fatorial confirmatória; foi encontrado um ajuste adequado à estrutura proposta pelo autor original. Os alfas de Cronbach e ordinais variaram de .77 a .87. Foram encontradas correlações positivas significativas entre o uso problemático generalizado da Internet, os sintomas psicopatológicos e o tempo de uso das redes sociais. As associações foram negativas com o bem-estar psicológico
Generalized Problematic Internet Use Scale 2: Adaptation for adults from Buenos Aires
Échelle d’utilisation problématique généralisée d’Internet 2: Adaptation pour les adultes de Buenos Aires
Keywords: Cyberpsychology; Internet psychology; Validity; Reliability; Cyberpsychologie; Psychologie de l’Internet; Validité; Fiabilité; Ciberpsicologia; Psicologia da internet; Validade; Confiabilidade; Ciberpsicología; Psicología de internet; Validez; Confiabilidad; https://purl.org/pe-repo/ocde/ford#5.01.00